Pemantauan Laju Arus Air Anak Sungai Kapuas di Tayan Hilir Berbasis IoT dan Nirkabel - Hermayandi, Muhammad Iqbal; Yacoub, Redi Ratiandi; Marpaung, Jannus (Universitas Harapan Medan, 2025)
Floods are natural disasters often caused by a combination of factors such as high rainfall, clogged waterways, overflowing upstream rivers, and various other geographical and environmental aspects. This research aims to develop a water flow monitoring system to provide accurate information to the public about potential flood occurrences. This method is based on Internet of Things (IoT) technology and long-range wireless communication technology (LoRa), which provides real-time access to water flow rate information. Based on the research, the water flow sensor has maximum and minimum limits. The pipe diameter of the water flow sensor significantly affects measurement results. Testing the transducer system in a pond using a water flow sensor can measure the water flow rate. Differences in accuracy and the impact of internet network instability cause data transmission delays from the receiver device to Blynk, as Blynk continuously provides notifications. Notifications can be sent by request or automatically triggered when the water flow rate reaches 0.3 m/s. The water flow monitoring information system is integrated through Telegram. Keywords: Blynk; Internet of Things; Long Range; Waterflow sensor; Monitoring System